PENGARUH STRESS KERJA DAN KOMPETENSI TERHADAP KINERJA KARYAWAN PADA PT. JASA HARAPAN BARAT (THE DISTRIBUTOR OF BADAK DRINK’S) - Putri Ulina Sitompul; Cut Rostina Fitria; Labora Natalia Purba (Lembaga Penelitian dan Pengabdian Kepada Masyarakat-Universitas Darma Agung. (LPPM_UDA), 2021)
The aim of this research was to find out the effect of working stress and employees’ competence on employees’ performance. This research was done at P.T. Jasa Harapan Barat. The population of sample was all employees of P.T. Jasa Harapan Barat which were seventy (70) employees. Method used was saturation sampling. Data collecting was done by using interview and survey with questioner as the tools. The nature of this research was explanatory research. The methods of analyzing data in this research were double linier regression analysis and classical assumption test. The result of the research showed that simultaneously and significantly working stress and competence had positive effect on the employees’ performance of P.T. Jasa Harapan Barat with the result of Fcount ≥ Ftable 6,767 ≥ 3,13 and significance of 0,002 ≤ 0,05. Partially working stress had positive and significant effect on the employees’ performance of P.T. Jasa Harapan Barat and competence had positive and significant effect on the employees’ performance of P.T. Jasa Harapan Barat. The result of the analysis of coefficient of determination obtained the adjusted value of R Square (R2) which showed the variation of employees’ performance variable which could be explained by the variation of working stress and competence variables as much as 14,3% meanwhile, the rest which was as much as 85,7% was explained by the variation of other variables.